A Review of Diopatra Ecology: Current Knowledge, Open Questions, and Future Threats for an Ecosystem Engineering Polychaete - Sarah K. Berke (Biology, 2022)
A well-known example of marine ecosystem engineering is the annelid genus Diopatra, which builds large tubes in coastal sediments worldwide. Early studies of Diopatra were among the first to recognize the importance of facilitation in ecology, and Diopatra has become a key marine soft-sediment application of the ecosystem engineering concept. Here, I review our current knowledge of Diopatra ecology, including its natural history, ecosystem engineering effects, and trophic relationships. I particularly explore how human activities are influencing Diopatra in terms of climate change, bait fishing, and species invasions. Most of what we know about Diopatra ecology comes from focal studies of a few species in a few well-known regions. Further evaluating how our current understanding applies to other species and/or other regions will help to refine and deepen our understanding of structure and function in marine systems.